2013
DOI: 10.4102/sajip.v39i2.1143
|View full text |Cite
|
Sign up to set email alerts
|

Work-family enrichment and psychological health

Abstract: Orientation: This study examines the beneficial aspects of the interface between work and family and its relationships with psychological health from a positive psychology perspective.Research purpose: The objective of this study was to investigate whether work-family enrichment helps to predict psychological health, specifically increased subjective well-being and decreased feelings of emotional exhaustion and depression.Motivation for the study: The burgeoning literature on the work-family interface contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 47 publications
2
23
0
1
Order By: Relevance
“…However, while there is growing evidence on the importance of family support on augmenting the performance of women entrepreneurs (Mari et al, 2016; McNall et al, 2010; Powell & Eddleston, 2013; Roger, 2005), enough is not known about the impact that FWE has on the performance of women-owned business in developing countries, as it has been widely neglected in prior studies (De Klerk, Nel, Hill, & Koekemoer, 2013; De Klerk, Nel, & Koekemoer, 2015; Jaga, Bagraim, & Williams, 2013; Marais, De Klerk, Nel, & De Beer, 2014; Langeveldt, 2016; Solomon, 2015; Wallace, 2015). This is because these researchers have primarily focused on how enrichment from the family domain affects employees as opposed to entrepreneurs.…”
mentioning
confidence: 99%
“…However, while there is growing evidence on the importance of family support on augmenting the performance of women entrepreneurs (Mari et al, 2016; McNall et al, 2010; Powell & Eddleston, 2013; Roger, 2005), enough is not known about the impact that FWE has on the performance of women-owned business in developing countries, as it has been widely neglected in prior studies (De Klerk, Nel, Hill, & Koekemoer, 2013; De Klerk, Nel, & Koekemoer, 2015; Jaga, Bagraim, & Williams, 2013; Marais, De Klerk, Nel, & De Beer, 2014; Langeveldt, 2016; Solomon, 2015; Wallace, 2015). This is because these researchers have primarily focused on how enrichment from the family domain affects employees as opposed to entrepreneurs.…”
mentioning
confidence: 99%
“…Stress and work-family conflict are intertwined; and this kind of conflict has been documented as both cause and outcome of job stress. It can have adverse effects on a person's well-being, leading to feelings of burnout, anxiety and exhaustion, insomnia and even poor selfesteem and depression (Allen et al, 2000;Barling et al, 2005;Jaga et al, 2013;Mathew and Panchanatham, 2011). Understanding the relationship between workfamily conflict and employees' well-being is therefore important in order to discover how working mothers can be supported to cope with work demands and family demands.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several authors have provided valuable information on the variables related to work-family interaction, including Coetzer (2006), De Klerk et al (2013, Franks et al (2006), Jaga et al (2013), Koekemoer and Mostert (2006), Mclellan andUys (2009), Mostert (2009), Oldfield and Mostert (2007), Van Aarde and Mostert (2008), and Van den Berg and Van Zyl (2008).…”
Section: Resources That Mitigate Negative Work-to-home Interference Amentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the meta-analysis conducted by McNall et al (2010) concluded that workfamily enrichment was positively associated with occupational satisfaction. Further research also attested to the existence of positive correlations between work-family enrichment and life satisfaction (Gabardo-Martins, Ferreira, & Valentini, 2016), subjective well-being (Jaga, Bagraim, & Williams, 2013) and occupational satisfaction (Fung, Ahmad, & Omar, 2014). Thus, based on the Work-Family Enrichment Model (Greenhaus & Powell, 2006), the Work Demands and Resources Model (Bakker & Demerouti, 2014) and the Social Exchanges Theory (Blau, 1964), as well as on the empirical findings about the relations between work-family enrichment and occupational satisfaction, and seeking to extend these findings to the professional category of physicians, it was hypothesized that work-family enrichment is positively associated with the occupational satisfaction of physicians (H1).…”
mentioning
confidence: 97%